Wheat Development and Yield as Affected by Era of Variety Release and In-Furrow Fertilizer - R. E. Maeoka; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2019)
Limited information exists on the interaction between historical and modern wheat varieties and in-furrow fertilizer. Our objectives were to estimate grain yield and differences in dynamics of biomass accumulation of historical and modern winter wheat varieties as affected by different fertilization practices. Two field trials were established during the 2017–2018 growing season in Kansas. Eight winter wheat varieties released between 1920 and 2016—Kharkof (1920), Scout 66 (1966), Karl 92 (1988), Jagger (1994), Jagalene (2001), Fuller (2006), KanMark (2014) and Larry (2016)—were sown using one of two different fertilizer treatments: either the university recommendation (control with no in-furrow fertilizer due to high testing soil-P levels) or a treatment where 100 lb/a MESZ were applied in-furrow. Grain yield was greater in semi-dwarf varieties relative to tall varieties. In-furrow fertilizer showed greater grain yield in comparison with no fertilizer treatment. Whole plant biomass accumulation at maturity did not change over decades. In-furrow fertilizer presented larger biomass accumulation than no fertilizer treatment. Harvest index increased from tall to semi-dwarf varieties. More site-years of this study are needed to determine whether there is a need for re-evaluation of current fertility recommendations for semi-dwarf wheat varieties, considering that no interaction between variety and fertility was observed.
Keywords: wheat; year of release; historical trends; in-furrow fertilizer; semi-dwarf